A novel nomogram for identifying high-risk patients among active surveillance candidates with papillary thyroid microcarcinoma - Zhang, Li; Wang, Peisong; Li, Kaixuan; Xue, Shuai (Frontiers in Endocrinology, 2023)
Objective Active surveillance (AS) has been recommended as the first-line treatment strategy for low-risk (LR) papillary thyroid microcarcinoma (PTMC) according to the guidelines. However, preoperative imaging and fine-needle aspiration could not rule out a small group of patients with aggressive PTMC with large-volume lymph node micro-metastasis, extrathryoidal invasion to surrounding soft tissue, or high-grade malignancy from the AS candidates. Methods Among 2,809 PTMC patients, 2,473 patients were enrolled in this study according to the inclusion criteria. Backward stepwise multivariate logistic regression analysis was used to filter clinical characteristics and ultrasound features to identify independent predictors of high-risk (HR) patients. A nomogram was developed and validated according to selected risk factors for the identification of an HR subgroup among “LR” PTMC patients before operation. Results For identifying independent risk factors, multivariable logistic regression analysis was performed using the backward stepwise method and revealed that male sex [3.91 (2.58–5.92)], older age [0.94 (0.92–0.96)], largest tumor diameter [26.7 (10.57–69.22)], bilaterality [1.44 (1.01–2.3)], and multifocality [1.14 (1.01–2.26)] were independent predictors of the HR group. Based on these independent risk factors, a nomogram model was developed for predicting the probability of HR. The C index was 0.806 (95% CI, 0.765–0.847), which indicated satisfactory accuracy of the nomogram in predicting the probability of HR. Conclusion Taken together, we developed and validated a nomogram model to predict HR of PTMC, which could be useful for patient counseling and facilitating treatment-related decision-making.